1999
DOI: 10.1037/0090-5550.44.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Understanding exercise motivation in colorectal cancer patients: A prospective study using the theory of planned behavior.

Abstract: The purpose of the present study was to evaluate the theory of planned behavior (I. Ajzen, 1991) as a framework for understanding exercise motivation in cancer patients. Participants were 66 postsurgical colorectal cancer patients who completed a baseline questionnaire that assessed exercise prediagnosis, demographic and medical variables, and the theory of planned behavior. Postsurgical exercise was self-monitored over a 4-month period and reported by telephone on a monthly basis. Hierarchical regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 17 publications
10
66
2
Order By: Relevance
“…According to the theory of planned behavior, the attitude towards exercise was the only variable that was related to the intention to exercise, which in turn, was linked to performing more post-surgery physical activity (Courneya et al, 1999b). With regard to beliefs (Speed-Andrews et al, 2014), thinking that physical activity would improve one's physical condition, energy level, and well-being was associated with performing more physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the theory of planned behavior, the attitude towards exercise was the only variable that was related to the intention to exercise, which in turn, was linked to performing more post-surgery physical activity (Courneya et al, 1999b). With regard to beliefs (Speed-Andrews et al, 2014), thinking that physical activity would improve one's physical condition, energy level, and well-being was associated with performing more physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, some studies have found higher levels of perceived selfefficacy in patients who perform more physical activity (Hawkes et al, 2015). On the other hand, based on the theory of planned behavior, Courneya et al (1999b) found that the intention to exercise and exercise pre-diagnosis were related to post-surgery exercise. Moreover, the attitude towards exercise was the only variable that correlated significantly with the intention to exercise.…”
Section: Motivational Factorsmentioning
confidence: 99%
“…The SEP intervention is guided by the theory of planned behavior (TPB; ref. 17) which has been validated for predicting and understanding exercise behavior in colorectal cancer survivors (15,(18)(19)(20). The counseling sessions cover 17 evidencebased behavior change techniques (Table 2; refs.…”
Section: Interventionsmentioning
confidence: 99%
“…Such constructs are central to the health belief model (Rosenstock, 1974), theory of reasoned action (Ajzen & Fishbein, 1980), and social cognitive theory (Bandura, 1986). Constructs from these models have been shown in prospective studies to be causally antecedent to health behaviors (e.g., Courneya, Friedenreich, Arthur, & Bobick, 1999;Quine, Rutter, & Arnold, 2000).…”
Section: Affective Associations With Health Behaviorsmentioning
confidence: 99%